Informal workers across Europe: Evidence from 30 countries - Mihails Hazans (Institute for the Study of Labor (IZA), 2011)
The European Social Survey data are used to analyze informal employment at the main job in 30 countries. Overall, informality decreases from South to West to East to North. However, dependent work without contract is more prevalent in Eastern Europe than in the West, except for Ireland, the UK and Austria. Between 2004 and 2009, no cases found when unemployment and dependent informality rates in a country went up together, suggesting that work without contract is pro-cyclical in Europe. Dependent informality rate is inversely related to skills (measured by either schooling or occupation). The low-educated, the young (especially students), the elderly, and persons with disabilities are more likely to work informally, other things equal. In Southern and Western Europe, immigrants from CEE and FSU feature the highest dependent informality rate, whilst in Eastern Europe this group is second after minorities without immigrant background. In Eastern, Southern and part of Western Europe, immigrants not covered by EU free mobility provisions are more likely to work without contracts than otherwise similar natives. We provide evidence that exclusion and discrimination play important role in pushing employees into informality, whilst this seems not to be the case for informal self-employed. Both on average and after controlling for a rich set of individual characteristics, informal employees in all parts of Europe are having the largest financial difficulties among all categories of employed population (yet they fare much better than the unemployed and discouraged), whilst informal self-employed are at least as well off as formal employees.
urn:nbn:de:101:1-201108092985
Keywords: J21; J24; J61; J71; O17; O52; 330; informal employment; human capital; discrimination; minorities; immigrants